Urinary incontinence in women and girls – rules of conduct in the primary care physician’s clinic - Rechberger, Tomasz; Kulik-Rechberger, Beata (Lekarz POZ, 2018)
The task of the lower urinary tract (LUT), composed of the bladder and urethra and urethral sphincters, is collection of urine and its elimination, in a controlled and socially acceptable manner. Uncontrolled leakage, in accordance with current terminology called incontinence, is embarrassing, makes life difficult and definitely reduces its quality. Thanks to a new approach to the problem as well as progress that has been made in diagnosis and treatment of LUT dysfunction in recent years, in many patients this condition can be effectively treated.